Optimalisasi Peran Regulasi dalam Upaya Pencegahan Peredaran Doping Melalui Marketplace Online di Indonesiasia - Anam, Mohammad Choirul (WELFARE STATE Jurnal Hukum, 2025)
This study aims to determine the role of regulation on the prevention of doping circulation through the marketplace and the optimisation of the application of regulations to prevent doping circulation in the marketplace in Indonesia. The method used in this research is normative juridical method with statutory approach and conceptual approach. Based on the results of the study, it shows that existing regulations have not been fully effective in preventing the circulation of doping through online marketplaces in Indonesia due to weak supervision, lack of education, and lack of antidoping test facilities. So that in order to optimise the application of regulations to prevent the circulation of doping in the marketplace in Indonesia, it is necessary to develop resources and technology through collaboration between institutions, provide insight to increase awareness about the dangers of doping through socialisation activities, and provide doping testing facilities that can be used by athletes to the regional level by developing a domestic anti-doping testing laboratory accredited by the World Anti-Doping Agency (WADA).